Aerodynamic Design and Performance Analysis of a Large-Scale Composite Blade for Wind Turbines - Semyoung Lim; Sungjin Ahn; Hyunbum Park (Applied Sciences)
In this study, we determined an aerodynamic configuration to design structures applying composites for large-scale horizontal-axis wind turbine blades. A new aerodynamic and structural design method for large wind turbine blades is presented. The rated power of the wind turbine blade is 25 MW class. The tip speed ratio is 7. The diameter of the designed blade is 260 m. Therefore, thick airfoils were selected to design large-scale wind turbine blades considering structural stiffness and maximum lift coefficients. For the aerodynamic design method, it was designed with the optimal angle of attack having the maximum lift-to-drag ratio. The blade element theory and vortex theory were applied to aerodynamic design. For the aerodynamic design results, its validity was investigated via aerodynamic performance analysis. As a result of analyzing aerodynamic performance, it was confirmed that higher power was generated. At 12.5 m/s of rated wind speed, electrical power was 28.32 MW. The structural design considering the aerodynamic design results was carried out. The composite laminate theory was adopted. Structural safety was evaluated for the designed blades. Finally, the structural design results were analyzed as sufficiently valid.